DETERMINING FACTORS IN OPTIMIZING THE UTILIZATION OF FISH RESOURCES IN THE COASTAL AREAS OF JEMBER REGENCY - R. Abdoel Djamali; Dhanang Eka Putra; Deltaningtyas Tri Cahyaningrum; Naning Retnowati; Amalia Dwi Marseva (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Jember Regency is directly adjacent to the Indian Ocean and boasts a coastline of about 170 km along the southern coast of East Java. The districts of Puger, Ambulu, Gumukmas, and Kencong have the most potential for marine fisheries in this area. The primary location for fishing operations, fish landings, and the distribution of marine goods is the Puger Coastal Fisheries Port (PPP). More than 80% of the total marine capture fisheries production in Jember Regency comes from lemuru (Sardinella lemuru), lisong tuna (Euthynnus affinis), and scad (Decapterus spp.). Finding the key elements for maximizing fish resources in Jember Regency's coastal regions is the aim of this study. The methodology employed is a descriptive exploratory approach with an expert system component. The analysis technique used is cognitive mapping analysis. This research concludes that: of the 17 factors identified, they can be classified as follows: (a) In order of priority, the following key factors directly and indirectly influence other factors that determine the direction of fish resource utilization: the income of fishermen, business groups, mutual cooperation and deliberation, the lack of large-scale industries processing captured fisheries products, the employment opportunities provided by fish processing SMEs in coastal areas, and landowners acting as leasing companies or loan sharks, (b) The income of fishermen, landowners acting as leasing companies or loan sharks, business groups, discussion and collaboration, the lack of large-scale industries processing captured fisheries products, fish processing SMEs as job opportunities in coastal areas, and landowners acting as leasing companies or loan sharks are the dominant factors that directly affect other factors, in order of priority.